2019
DOI: 10.1177/2472555218796656
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G-Quadruplex-Binding Inhibitors of Myc Expression through Affinity Selection–Mass Spectrometry

Abstract: The Myc oncogene is overexpressed in many cancers, yet targeting it for cancer therapy has remained elusive. One strategy for inhibition of Myc expression is through stabilization of the G-quadruplex (G4), a G-rich DNA secondary structure found within the Myc promoter; stabilization of G4s has been shown to halt transcription of downstream gene products. Here we used the Automated Ligand Identification System (ALIS), an affinity selection-mass spectrometry method, to identify compounds that bind to the Myc G4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In fact, DNA G-quadruplexes previously screened in ALIS also resulted in a high number of binding compounds. 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, DNA G-quadruplexes previously screened in ALIS also resulted in a high number of binding compounds. 26…”
Section: Resultsmentioning
confidence: 99%
“…In fact, DNA G-quadruplexes previously screened in ALIS also resulted in a high number of binding compounds. 26 Though the ALIS platform was able to identify small molecule binders for diverse RNA targets, we wondered whether the observed low hit rate across targets was due to inherent bias in the interrogated screening libraries that are traditionally used for protein-targeted drug discovery. The Functionally Annotated Library, assembled using pharmacogenomic data, and the Diversity Library, assembled from synthetic and commercial acquisition efforts, have historically both been applied toward the discovery of proteinbinding ligands.…”
Section: Initial Alis Screening and Building Of A Small Molecule Rna mentioning
confidence: 99%
“…One attractive route to pharmacological inhibition of MYC has been the prevention of its expression through small‐molecule‐mediated stabilization of the G‐quadruplex present in its promoter (Felsenstein et al, 2016). Using the ALIS‐based screen system, Flusberg et al (2019) identified 10 hits that selectively bound to the Myc G‐quadruplex from a set of ~50,000 compounds. Binding affinities were determined using the ALIS ligand titration method.…”
Section: Indirect Ba‐ms Methods Relying On Size Exclusion Chromatographymentioning
confidence: 99%
“…126,[129][130][131] Recently, Merck (Kenilworth, NJ) applied their AS-MS method, referred to as the Automated Ligand Detection System (ALIS), to screen compounds against numerous RNA targets, an approach validated with ncRNA riboswitches, their ligands, and a large unbiased smallmolecule library. [132][133][134] Here, RNA is incubated with mass-encoded small-molecule mixtures, small molecule-RNA complexes are purified by size exclusion chromatography (SEC), and the complexes dissociate through reverse-phase chromatography. Bound ligands are detected by high-resolution MS (Fig.…”
Section: Ms-based Approachesmentioning
confidence: 99%